An Ellagic Acid Derivative and Its Antioxidant Activity of Stem Bark Extracts of Syzygium polycephalum Miq. (Myrtaceae) - Tukiran Tukiran; Andika Pramudya Wardana; Nurul Hidayati; Kuniyoshi Shimizu (Indonesian Journal of Chemistry, 2018)
The investigation of the Syzygium polycephalum Miq. (Myrtaceae) aimed to assess the phytochemical contents and antioxidant activity of the chloroform fraction. In this study, the fraction was obtained from methanol extract of S. polycephalum stem bark partitionated by chloroform. An ellagic acid derivative was successively isolated from the chloroform fraction. The molecular structure of isolated compound was elucidated and established as 3,4,3’-tri-O-methylellagic acid through extensive spectroscopic studies including UV-Vis, FTIR, NMR and LC-MS analyses and by comparison with literature data. The finding of the isolated compound is the first time from the plant, although the isolated compound previously have been found in the other Syzygium species such as S. cumini together with ellagic acid and 3,3’-di-O-methylellagic acid. The chloroform fraction, isolated compound, and vitamin C showed antioxidant activity against 2,2’-diphenyl-1-picrylhydrazyl (DPPH) with IC50 value of 163.6, 72.1, and 11.5 μg/mL, respectively.